2013
DOI: 10.1021/nn4035519
|View full text |Cite
|
Sign up to set email alerts
|

Swift Nanopattern Formation of PS-b-PMMA and PS-b-PDMS Block Copolymer Films Using a Microwave Assisted Technique

Abstract: Microphase separation of block copolymer (BCPs) thin films has high potential as a surface patterning technique. However, the process times (during thermal or solvent anneal) can be inordinately long, and for it to be introduced into manufacturing, there is a need to reduce these times from hours to minutes. We report here BCP self-assembly on two different systems, polystyrene-b-polymethylmethacrylate (PS-b-PMMA) (lamellar- and cylinder-forming) and polystyrene-b-polydimethylsiloxane (PS-b-PDMS) (cylinder-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 65 publications
(101 reference statements)
1
87
0
Order By: Relevance
“…Directed self-assembly of PS-b-PDMS on topographic patterns has been demonstrated in a number of articles [3,4,19,21,[32][33][34][35][36][37][38]. Further, Buriak et al has shown the effectiveness of microwave assisted method to guide cylinder-forming PS-b-PMMA and PS-b-P4VP BCPs on topographically patterned substrates [39].…”
Section: Directed Self-assembly By Microwave Irradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Directed self-assembly of PS-b-PDMS on topographic patterns has been demonstrated in a number of articles [3,4,19,21,[32][33][34][35][36][37][38]. Further, Buriak et al has shown the effectiveness of microwave assisted method to guide cylinder-forming PS-b-PMMA and PS-b-P4VP BCPs on topographically patterned substrates [39].…”
Section: Directed Self-assembly By Microwave Irradiationmentioning
confidence: 99%
“…This was followed by an O2 plasma etch to remove PS and affect oxidation of the PDMS to yield silica-like topographies indicative of the original BCP pattern. These steps follow similar methodology developed by Ross et al [17] and full etch details are available elsewhere [3,4,[18][19][20].…”
Section: Plasma Etching Of Bcp Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Industrial demands for acceptable lithographic applications request the DSA process within 240 seconds [13,17]. The solvothermal method [18], microwave annealing method [19], and rapid thermal annealing method [20,21] are studied to shorten a DSA process period.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of microwave has been demonstrated with poly(styrene-b-dimethylsiloxane) (PS-b-PDMS) system. 9 However, despite the promise of this technique, little is known about the mechanism of how microwave irradiation might sponsor the molecular motion that accompanies microphase separation. Buriak and coworkers have championed substrate heating as the primary source of molecular motion driven by defects in silicon substrates that absorb microwave radiation.…”
Section: Introductionmentioning
confidence: 99%